Examining the compliance of hospitality services in KLIA Malaysia with Maqasid al-Shariah - Zakariyah, Luqman; Zakaria, Mohamad Sabri; Abd Rahman, Mohamad Zulkifli (2018)
ABSTRACT This study aimed to investigate the hospitality services at the Kuala Lumpur International Airport 1 (KLIA 1). Specifically, it attempted to examine hospitality in Islamic law, the hospitality services offered at the airport and the extent to which they were in line with Maqasid al-Sharia (the intent of Islamic law). To achieve these objectives, inductive method was used to gather information about hospitality and Maqasid al-Shari’ah from classic and modern books. Survey method was also used to collect data by questionnaire from tourists at the aforementioned airport, and foreign students and workers residing in Malaysia. Descriptive analytical method was then used to discuss the data collected from the two sources. This research ended with the conclusions that the hospitality services at the airport achieved some objectives of the Islamic law such as taysir (alleviation), cooperation and respect for human rights, and that the implementation of hospitality services which suits Maqasid al-Shari’ah plays a pivotal role in attracting tourists as the Maqasid al-Shari’ah is based on fitrah, which exists in every human being.